Pengaruh Pelayuan dan Suhu Pengeringan Daging Buah Nanas pada Aalat Pengering Vakum terhadap Mutu Produk yang Dihasilkan - Ramendra Wiro Ginting; Ida Bagus Putu Gunadnya; I.A. Rina Pratiwipudja (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2016)
The purpose of this research was to measure the quality of dried pineapple pulp resulting from pre-drying treatment and method of drying, which done using randomized complete block design with factorial experiments. The first factor was pre-drying treatment consisted of two treatments, namely with and without blanching and the second one was method of drying such as control, vacuum drying at 60 oC,70o C, and 80 oC. The experiment was repeated three times. The results of the experiment showed that the best treatment resulting dried pineapple pulp with the highest organoleptic values was interaction between fruit pulp without blanching and employing vacuum drying at 70oC. The organoleptic values of this dried pineapple pulp based on its colour, crispiness, and taste were 5.70, 4,20, and 5.35, respectively.